Transmediality: A Model in Global Nineteenth-Century Studies. Issue 1 (1st June 2022) - Pietrzak-Franger, Monika
Abstract : I argue that the nineteenth century is particularly pertinent to our understanding of transmediality and, moreover, that transmediality offers a valuable framework to rethink and study the period itself. In what follows, then, I sketch some of the advantages of what I call nineteenth-century transmedia studies, and of global transmedia studies in particular. I begin by outlining how a focus on transmediality transforms our understanding of the era. Against this backdrop, I show the value of transmedia practices for global nineteenth-century studies, and, last but not least, spotlight some of the implications this may have for the shape of future nineteenth-century scholarship and funding.